2008
DOI: 10.1097/gme.0b013e31815c1e7f
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones in the management of postmenopausal osteoporosis

Abstract: This is a review article designed to address the effects of soy isoflavones on bone metabolism in postmenopausal women and their place in the prevention and treatment of postmenopausal osteoporosis. Soy isoflavones are natural products that could be used as an alternative to menopausal hormone therapy because they are structurally and functionally related to 17beta-estradiol. In vitro and animal studies have shown that they act in multiple ways to exert their bone-supporting effects. They act on both osteoblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 81 publications
1
60
0
6
Order By: Relevance
“…Through stimulating bone formation and inhibiting bone reabsorption, isoflavones can maintain bone health. Human studies including observational and clinical trial studies also support favorable effects of isoflavones showing the results such as increasing bone mineral density and bone mechanical strength, and inhibiting bone turnover in postmenopausal women (Atmaca et al, 2008). Ingestion of isoflavones (more than 90 mg/day of isoflavones) at least 6 months have a significant effect for increasing spine bone mineral density in meta-analyses for randomized controlled trials however the effects on hip and leg bones are controversial (Taku et al, 2010).…”
Section: Bone Healthmentioning
confidence: 99%
“…Through stimulating bone formation and inhibiting bone reabsorption, isoflavones can maintain bone health. Human studies including observational and clinical trial studies also support favorable effects of isoflavones showing the results such as increasing bone mineral density and bone mechanical strength, and inhibiting bone turnover in postmenopausal women (Atmaca et al, 2008). Ingestion of isoflavones (more than 90 mg/day of isoflavones) at least 6 months have a significant effect for increasing spine bone mineral density in meta-analyses for randomized controlled trials however the effects on hip and leg bones are controversial (Taku et al, 2010).…”
Section: Bone Healthmentioning
confidence: 99%
“…Epidemiological and clinical studies of postmenopausal women have suggested that isoflavones decrease their risk of osteoporosis and cardiovascular diseases while alleviating vasomotor symptoms [4][5][6][7][8]. However, the beneficial effects of isoflavones remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The isoflavones are therefore considered to be possible selective estrogen receptor modulators, which may bind to estrogen receptors and selectively stimulate or inhibit estrogen-like action in various tissues. 2 Given that soy-based foods are now more frequently consumed than was previously the case, both as an alternative approach to treating the symptoms of menopause and for promoting cardiovascular health, 3,4 concerns have arisen about the intake of these compounds by patients with hormone-sensitive breast cancer, in whom tumour growth depends largely on estrogen. Tamoxifen and anastrozole are commonly used as adjuvant endocrine therapy for hormone-sensitive breast cancer, and these drugs are effective in preventing recurrence and prolonging survival.…”
mentioning
confidence: 99%